Accounting History from the Renaissance to the Present: A Remembrance of Luca Pacioli (Book). - Langenderfer, Harold Q.; Williams, Thomas H. (The Accounting Review, 1997)
Reviews the book "Accounting History From the Renaissance to the Present: A Remembrance of Luca Pacioli," edited by T.A. Lee, A. Bishop and R.H. Parker.